2016
DOI: 10.4103/0976-3147.178670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of substance abuse among regular degree health science students in Sheba University College in Mekelle Town, Tigray - Ethiopia

Abstract: Background:Substance abuse (SA) refers to the harmful or hazardous use of psychoactive substances, including alcohol and illicit drugs. The most common substances which are usually abused are alcohol and tobacco. Herein, we assessed the prevalence of SA among regular degree health science students of the Sheba University College (SUC).Materials and Methods:A cross-sectional survey was carried out among 1076 SUC students using self-administered structured questionnaire. The simple sampling technique was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
(20 reference statements)
3
13
3
Order By: Relevance
“…In this study, a total of 7,861 study participants were included from 13 studies. ese studies were carried out from January 2011 to December 2018 from 10 different universities in seven regions of the country: Addis Ababa � 1, Amhara � 3, Dire Dawa � 1, Oromia � 1, Somali � 2, SNNPR � 3, and Tigray � 1 [22][23][24][25][26][27][28][29][30][31][32][33][34]. All of the studies included were cross-sectional with a sample size ranging from 271 to 1022 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In this study, a total of 7,861 study participants were included from 13 studies. ese studies were carried out from January 2011 to December 2018 from 10 different universities in seven regions of the country: Addis Ababa � 1, Amhara � 3, Dire Dawa � 1, Oromia � 1, Somali � 2, SNNPR � 3, and Tigray � 1 [22][23][24][25][26][27][28][29][30][31][32][33][34]. All of the studies included were cross-sectional with a sample size ranging from 271 to 1022 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A similarly high lifetime prevalence of substance use has been reported at other Universities in Ethiopia: 62.4% at Haramaya University [25], 45% at Sheba University College at Mekelle [26] and 64% at Dire Dawa University [14]. One study among college students in Western Kenya revealed a slightly higher (70%) lifetime prevalence of psychoactive substance use [27].…”
Section: Discussionmentioning
confidence: 61%
“…Our finding that males are more likely to report current psychoactive substance use has been found before [15,16,19,20,[25][26][27][28]. The WHO (2011) reports a fivefold greater risk of death attributable to substance use [37] and a twofold greater risk of substance use disorder [38] among men than women.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations